Find m so that: (2/9)^3*(2/9)^6=(2/9)^2m-1

what
  • -1
what is that??
  • -2
I don't know anything about that.
But can you just put a vote to this answer please!
  • -2
i dont no








































































































































 
  • -1
HHAHAHAHHA
  • 0
Very tough
 
  • 1
m=5
  • -1
think m=5
  • 0
(2/9)^3 * (2/9)^6 = (2/9)^2m-1
{ In multiplication when the base is same, powers are added }  (2/9)^3+6 = (2/9)^2m-1
{ when there is an '=' sign in , the powers are equal}    9 = 2m-1
9+1 = 2m
10 = 2m 
10/2 = m 
5 = m
  • 0
What are you looking for?